THE RELATIONSHIP BETWEEN STRESS LEVELS IN TYPE II DIABETES MELLITUS PATIENTS WITH DIABETIC ULCERS IN KOLANG HEALTH CENTER 2021 - Dedi Mizwar Tarihoran; Pius Kosmas; Faziah Faziah (Institute of Computer Science (IOCS), 2022)
Stresslevelisastimulusthatcancauseanimbalanceinindividualhomeos tasis,bothphysiologically and psychologically. The risk of diabetic ulcers is a condition in which infectionis found in the ulcer and/or its distruction to the deepest skin tissue on the feet in patients withdiabetes mellitus due to nerve abnormalities and peripheral arterial blood vessel disorders. atthe Kolang Health Center. The research method uses a descriptive analytic design with a crosssecti onal design. The results of this study showed that there were 5 respondents with mild stress(21.7%),moderatestress13peo ple(56.5%)and5peoplewithseverestress(21.7%). Inaddition, there were 2 respondents with low risk of diabetic ulcers (8.7%), 10 people (43.5%)moderate diabetic ulcer risk and 11 people (47.8%) high risk respondents. In this study, inaddition to stress levels, the results of measurements of abnormal blood sugar levels were alsofound in 17 respondents (73.9%). Statistical results using the Chi Square test indicate that theAsmip.Sig value is 0.020, which means the asimp.sig value is 0.020<0.05, it can be concludedthatthe reisarelationshipbetweenstresslevelsandtheriskofdiabeticulcers.Th enextstepis tofurtherexamineanddeepeninsightintostresslevelswith theriskofdiabeticulcersandisexpectedfor further researchers.